Evidence for a Key Role of Cytochrome bo(3) Oxidase in Respiratory Energy Metabolism of Gluconobacter oxydans - Richhardt, Janine (American Society for Microbiology, 2013)
The obligatory aerobic acetic acid bacterium Gluconobacter oxydans oxidizes a variety of substrates in the periplasm by membrane-bound dehydrogenases, which transfer the reducing equivalents to ubiquinone. Two quinol oxidases, cytochrome bo(3) and cytochrome bd, then catalyze transfer of the electrons from ubiquinol to molecular oxygen. In this study, mutants lacking either of these terminal oxidases were characterized. Deletion of the cydAB genes for cytochrome bd had no obvious influence on growth, whereas the lack of the cyoBACD genes for cytochrome bo(3) severely reduced the growth rate and the cell yield. Using a respiration activity monitoring system and adjusting different levels of oxygen availability, hints of a low-oxygen affinity of cytochrome bd oxidase were obtained, which were supported by measurements of oxygen consumption in a respirometer. The H(+)/O ratio of the ΔcyoBACD mutant with mannitol as the substrate was 0.56 ± 0.11 and more than 50% lower than that of the reference strain (1.26 ± 0.06) and the ΔcydAB mutant (1.31 ± 0.16), indicating that cytochrome bo(3) oxidase is the main component for proton extrusion via the respiratory chain. Plasmid-based overexpression of cyoBACD led to increased growth rates and growth yields, both in the wild type and the ΔcyoBACD mutant, suggesting that cytochrome bo(3) might be a rate-limiting factor of the respiratory chain.